Analysis of performance of the karate punch (gyaku-zuki). - Suwarganda, E.; Razali, R.; Wilson, B.; Ponniyah, A.; Flyger, N. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Variation in the movement sequence of the reverse punch (Gyaku-zuki) could affect kinematic variables such as punch time, distance and joint velocities. The reverse punches of nine elite Malaysian karate athletes were imaged in 3D at 150 Hz for two conditions (Jodan and Counter-chudan). Based on the linear resultant joint velocities of the shoulder and elbow two clusters are identified. One cluster is characterized by a more simultaneous movement sequence and the other by a more sequential movement sequence. The first cluster is mostly associated with female performances (87%) and the second cluster mostly with male performances (83%). It is found that the mostly male cluster achieved longer punch distance and higher peak linear resultant joint velocities for shoulder, elbow and wrist. Furthermore subgroups within the two clusters are identified and are associated with Jodan and Counter-chudan punches. The mostly female cluster achieves longer punch distance and higher peak linear resultant velocities in the subgroup associated with Jodan punches. However, the mostly male cluster achieves similar results for the subgroup associated with the Counter-chudan. Conclusion: the females tend to punch with a simultaneous sequence and men tend to punch with a sequential sequence with regard to the shoulder and elbow movements. Additionally women and men seem to have optimal performances in terms of punch distance and peak linear resultant joint velocities in different punching conditions.